Legal Certainty of Lease Rights for Foreign Citizens of Ownership Land in Indonesia - Iswara, Yudha Tri Dharma; Widhiyanti, Hanif Nur; Dian Ph, Novitasari (Faculty of Law, Universitas Pattimura, 2024)
Introduction: In Indonesia, regulations have been issued that guarantee certainty over land in Indonesia, one of which is Law Number 5 of 1960 concerning Basic Agrarian Law, which was subsequently derived using Government Regulation Number 10 of 1961 concerning Land Registration and replaced by Government Regulation Number 24 of 1997 concerning Land Registration, Foreign nationals who have an interest in investing in Indonesia do not have a few lease agreements to lease land, especially in Bali, lease agreements in general regulations are regulated in Article 1548 of the Civil Code but because the lease period in Indonesia is not specifically regulated, So there is often a legal smuggling where a lease agreement has a long term, even indicating a lease for life. Therefore, the importance of legal certainty regarding the lease period is regulated in a law and regulation, so that in determining the period in the lease agreement still has a propriety and fairness in its implementation. Purposes of the Research: namely regarding the time limit for leasing for foreigners on land in Indonesia which needs a special regulation that is clearer and more detailed.Methods of the Research: The research method in this writing uses normative juridical legal research with a statutory approach, legal concept approach and case approach. In this thesis, the author discusses two legal issues related to legal certainty of lease time limits on freehold land in Indonesia for Foreign Nationals and legal consequences arising from the blurring of legal norms regarding arrangements related to lease time limits for freehold land in Indonesia.Results of the Research: The results showed that in terms of determining legal certainty related to the lease period for now, we can look for determining indicators regarding time limits. The consequences that arise when a lease agreement has a time limit that indicates a live well lease is a Non-Existent legal act.